Hemoglobin Enhancement in Pregnancy: A Study on Fe Tablets Combined with Green and Red Bean Juices - Lamana, Aspia; Fajrin, Dessy Hidayati; Sari, Nurmala; Kuswanti, Febti; Magdalena Sitorus, Sony Bernike; Khuzaifah, Khuzaifah (Poltekkes Kemenkes Palu, 2024)
Introduction: The proportion of anemia in pregnant women in Indonesia has increased from 37.1% to 48.9% in 2018. This study aimed to determine the difference in the effectiveness of combining green bean (Vigna radiata) or red bean (Vigna angularis) juice with iron (Fe) tablets on hemoglobin (Hb) levels in pregnant women in Pontianak City, Indonesia. Method: A quasi-experimental study with a two-group pretest-posttest design was conducted on 32 pregnant women in their second trimester, divided into two groups of 16 each. The intervention group received a combination of green bean juice (300 ml/day) and Fe tablets, while the control group received a combination of red bean juice and Fe tablets for 14 days. Hemoglobin levels were measured before and after the intervention. Data were analyzed using paired and independent t-tests with a 95% confidence level. Results: The results showed a significant difference in the increase of Hb levels between the intervention and control groups (p=0.01). The mean Hb level increased from 10.90 to 11.72 g/dL in the green bean group and from 10.78 to 12.41 g/dL in the red bean group. The combination of red bean juice and Fe tablets showed the highest mean difference in Hb levels (1.63 g/dL). Conclusions: In conclusion, both combinations of green bean or red bean juice with Fe tablets were effective in increasing Hb levels in pregnant women, with the red bean combination showing a higher effectiveness. These findings provide additional information for healthcare professionals in educating about legumes that can help increase blood Hb levels during pregnancy.